The Effectiveness of Picture Card Media on the Cognitive Abilities of Children Aged 5-6 Years - Khoirun Nisaa; Evie Palenewen; Berta Laili Khasanah (Journal of Practice Learning and Educational Development, 2026)
The use of media in early childhood learning is one way to support children's cognitive development. At Al Muhajirin Islamic Kindergarten in Samarinda, media use is not yet varied, resulting in underdevelopment of children's cognitive abilities. This study used a population of 75 and a sample of 30 children. The sampling technique used was purposive sampling. The research instruments used were RPPH, assessment rubric, and pretest-posttest questions. The cognitive development indicators assessed in this study were naming the number symbols 1-10, using number symbols to count, matching numbers with symbols, recognizing vowel and consonant symbols, representing objects in pictures/writing, recognizing differences based on size, and demonstrating exploratory and investigative activities. The results of this study before the treatment showed that 63% of students hadn't developed and 37% had begun to develop. After the treatment, the results were 23% developing as expected and 77% developing very well. The N-Gain Test results showed a prevalence of 0.76, which is categorized as high, indicating that the use of picture cards depicting Kalimantan animals is effective as a teaching variation material for teachers.